FINANCIAL MANAGEMENT BEHAVIOR ANALYSIS OF MSMEs AS SUPPORTING ADVANCEMENT COASTAL TOURISM IN MADURA - M. Boy Singgih Gitayuda; Moh. Zaki Kurniawan (SEAN Institute, 2023)
This research aims to determine (1) the effect of financial attitude on financial management behavior in SME actors in the coastal area of Madura, (2) the effect of income on financial management behavior in SME actors in the coastal area of Madura, (3) the effect of financial self-efficacy on behavior financial management of SME actors in the coastal area of Madura, (4) and the effect of financial attitude, income, and financial self-efficacy on financial management behavior on SME actors in the coastal area of Madura. The subjects of this study were all SME owners in the coastal area of Madura as many as 60 SMEs, with a probability sampling technique using the Slovin formula. The type of data used includes primary data and secondary data, with data collection techniques namely by interview, questionnaire (questionnaire), and observation. The data analysis technique used is multiple linear regression analysis, determinant coefficient test, hypothesis test. The results showed that financial attitude had a positive and significant effect on the financial management behavior of SME actors in the coastal tourism area of Madura, while income and financial self-efficacy had no significant effect on the financial management behavior of SME actors in the coastal tourism area. Meanwhile, simultaneously financial attitude, income, and financial self-efficacy affect the financial management behavior of SMEs in the Madura coastal tourism area.